The effectiveness of “Boteli” and Fed on exercises to court tennis backhand groundstroke rally skills - Rumi Doewes; Djoko nugroho (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and objective. Study aims to determine the effectiveness of Boteli exercises and fed on the groundstroke rally skills of backhand tennis in sports students.